Green synthesis of Ag nanoparticles using aqueous extract of Kaempferia galanga Linn. (Zingiberaceae) rhizomes (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
Green synthesis of noble metal nanoparticles (NPs) is a vast developing area of research. In the present study, silver nanoparticles (Ag-NPs) were rapidly synthesized by treating silver ions through a simple and green synthetic route using water extract of the rhizomes of Kaempferia galanga Linn.(KG), which acted simultaneously as a reductant and stabilizer. The reaction process was monitored using ultraviolet–visible (UV-Vis) spectroscopy. The  EPR spectra of AgKG NPs was found to be confined in a single line which showed  the presence of an unpaired electron indicating of  Ag in neutral state at room temperature. The size and morphology of AgNPs recorded by Scanning electron  microscopy (SEM) were further confirmed by transmission electron microscopy (TEM) and selected area electron diffraction (SAED). The formation of AgNPs is evidenced by the appearance of signatory brown colour of the solution. FT-IR spectrum indicates the presence of different functional groups in capping the nanoparticles with K. galanga. Average size range estimated from our studies is  2 to 4 nm. It consists of a spherical like particles.